Moments of drawing: an approach to the school context - Monsalve Pulido, Héctor Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This reflection article aims at reconstructing the meaning of drawing in order to make its reading possible in the school context. The emphasis is placed on the process of achievement called moment, defined as the active position of the concept of drawing. This perspective looks for a way to describe the process of development of graphic expression which appears at the school age, including the elements involved during its development. In this way the unilateral objectual position usually associated with children’s drawing is subverted. Through observation from a distance, by means of narrative description of moments, we are able to interact with the factors and procedures that achieve creation, which will be relevant for pedagogical analysis.